Analisis Kebutuhan Tenaga Rekam Medis Berdasarkan Beban Kerja Dengan Metode Workload Indicator Staffing Need (WISN) Di Puskesmas Cisayong Kabupaten Tasikmalaya - Pamungkasari, Tria; Paramarta, Vip; Rahmiyati, Ayu Laili (Innovative: Journal Of Social Science Research, 2024)
The purpose of this study was to evaluate the need for health workers at the Cisayong Health Center, Tasikmalaya Regency based on workload using the Workload Indicator Staffing Need technique. The purpose of this study was to determine and evaluate standard flexibility, standard workload estimation, and the determination of time and medical record staff units at the Cisayong Health Center UPTD. With the help of NVIVO analysis software, To describe the actual situation, This research methodology uses a qualitative approach. Primary and secondary data are used in this study. along with observations of all events and related papers related to the subject matter. The conclusion of the study shows that working hours have been calculated appropriately to ensure that medical record staff have access to the maximum amount of time needed to work. Consideration of the workload in each unit as well as human resource needs has been made to optimize the distribution of health workers. Based on calculations using the WISN method, Validation of workload standards ensures that these calculations are realistic and can be applied in the field. The time allocated for these various activities does not interfere with the availability of effective working time for medical record staff. Calculations using the method provide more accurate and objective results, so that the UPTD Cisayong Health Center can manage human resources more effectively. Keywords: Medical Record Power Requirements, Workload, Methods Workload Indicator Staffing Need (WISN)